Use of yeast cell wall extract as a tool to reduce the impact of necrotic enteritis in broilers. (11th March 2015) - M'Sadeq, Shawkat A.; Wu, Shu-Biao; Choct, Mingan; Forder, Rebecca; Swick, Robert A.
Abstract : The use of a yeast cell wall extract derived from Saccharomyces cerevisiae (Actigen ® ) has been proposed as an alternative to in-feed antibiotics. This experiment was conducted to investigate the efficacy of yeast cell extract as an alternative to zinc bacitracin or salinomycin using a necrotic enteritis challenge model. A feeding study was conducted using 480-day-old male Ross 308 chicks assigned to 48 floor pens. A 2 × 4 factorial arrangement of treatments was employed. The factors were: challenge (− or +) and feed additive (control, zinc bacitracin at 100/50 mg/kg, yeast cell wall extract at 400/800/200 mg/kg, or salinomycin at 60 mg/kg in starter, grower, and finisher, respectively). Diets based on wheat, sorghum, soybean meal, meat and bone meal, and canola meal were formulated according to the Ross 308 nutrient specifications. Birds were challenged using a previously established protocol (attenuated Eimeria spp oocysts) on d 9 and 10 8 to 10 9 Clostridium perfringens (type A strain EHE-NE18) on d 14 and 15). Challenged and unchallenged birds were partitioned to avoid cross contamination. Challenged birds had lower weight gain, feed intake and livability compared to unchallenged birds on d 24 and d 35 ( P < 0.05). Birds given zinc bacitracin, yeast cell wall extract, or salinomycin had improved weight gain and livability when compared to control birds given no additives. Challenge × additive interactions were observed for feed intake and weight gain on d 24 and d 35 ( P < 0.01). The additives all had a greater positive impact on feed intake, weight gain, and livability in challenged than unchallenged birds. All challenged birds showed higher necrotic enteritis lesion scores in the small intestine sections when compared to unchallenged birds ( P < 0.01). Birds fed yeast cell wall extract exhibited increased villus height, decreased crypt depth, and increased villus:crypt ratio when challenged. Yeast cell wall extract, zinc bacitracin, and salinomycin were effective in preventing performance decline from necrotic enteritis in the current study. This study indicates that yeast cell wall extract has promise as a tool for controlling necrotic enteritis.